Of Hedgehogs and Representation: Chasing Religious Persecution in Law - Ghanea, Nazila (The review of faith & international affairs, 2018)
We hear about 'religious persecution' with great regularity in recent years, but what is meant by it? Where there is a rallying call of 'religious persecution', what precisely is meant by that? Is there a minimum threshold for a situation qualifying as religious 'persecution'? Is it in fact occurring with greater regularity than in past decades or is it just being reported more? Is it increasingly politicized and, if so, why? This article analyzes these questions.